2020
DOI: 10.3390/ma13173907
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cyclic Loading Impact on the Creep Deformation Mechanism in Cohesive Materials

Abstract: Long-term cyclic loading is observed in a wide range of human activities, as well as in nature, such as in the case of ocean waves. Cyclic loading can lead to ratcheting which is defined as progressive accumulation of plastic deformation in a material. Long-term cyclic loading causes a time effect (creep), which is a secondary compression effect. In this article, we conducted 15 triaxial tests on four types of cohesive materials in undrained conditions to evaluate the damage and failure mechanism. To character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous studies by Głuchowski & Sas [40] and An et al [41] have suggested that soil stiffness is high at low cyclic stress levels but decays with an increase in high cyclic stress levels. In addition, their studies supported the fact that strain level increases with cyclic stress, hence resilient modulus decreases with an increase in cyclic stress.…”
Section: Effects Of Cyclic Stress On Resilient Modulusmentioning
confidence: 95%
“…Previous studies by Głuchowski & Sas [40] and An et al [41] have suggested that soil stiffness is high at low cyclic stress levels but decays with an increase in high cyclic stress levels. In addition, their studies supported the fact that strain level increases with cyclic stress, hence resilient modulus decreases with an increase in cyclic stress.…”
Section: Effects Of Cyclic Stress On Resilient Modulusmentioning
confidence: 95%
“…The ratchet strain rate decreases rapidly and reduces to nearly 0% in the 3rd cycle, after which the ratchet strain caused by stress cycling no longer increases. The lowest point of decreasing ratchet strain rate is also in the 3rd cycle, i.e., the plastic shakedown transition point, which indicates that the phenomenon of anelastic recovery not only slows down the accumulated creep strain rate, but also reduces the ratchet strain rate [28]. Because anelastic recovery can reduce the accumulation of creep damage in the material [29], which is one of the most important reasons for the specimen to exhibit plastic shakedown.…”
Section: The Evolution Of Strain Componentsmentioning
confidence: 96%
“…The ratchet strain rate decreases rapidly and reduces to nearly 0% in the 3rd cycle, after which the ratchet strain caused by stress cycling no longer increases. The lowest point of decreasing ratchet strain rate is also in the 3rd cycle, i.e., the plastic shakedown transition point, which indicates that the phenomenon of anelastic recovery not only slows down the accumulated creep strain rate, but also reduces the ratchet strain rate [29]. Because anelastic recovery can reduce the accumulation of creep damage in the material [30], this is one of the most important reasons for the specimen to exhibit plastic shakedown.…”
Section: The Evolution Of Strain Componentsmentioning
confidence: 99%